Central pontine myelinosis resulting in quadriplegis in alcohol withdrawal - Md Ralib, Azrina; Mohamed, Abdul Hadi; Md Dani, Noordini; Mohd Yatim, Asmarawati; Che Mohamed, Siti Kamariah (Confederation of ASEAN Societies of Anaesthesiology, 2009)

(untitled)
Central pontine myelinosis resulting in quadriplegis in alcohol withdrawal